PERAN KEPALA SEKOLAH SEBAGAI SUPERVISOR DALAM MENINGKATKAN MUTU PENDIDIKAN - ASTUTI ASTUTI (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2017)
This paper discusses the role of the principal as a supervisor in improving the quality of education. Principals as leaders of educational institutions should be responsible for all school / madrasah activities. He has full authority and responsibility to conduct all educational activities including supervision activities, both academic supervision and managerial supervision within the school / madrasah he leads. Principal As Supervisor serves to guide, assist and direct educators and educational staff to appreciate and implement the procedures of education to support the quality of education.This paper discusses the role of the principal as a supervisor in improving the quality of education. Principals as leaders of educational institutions should be responsible for all school / madrasah activities. He has full authority and responsibility to conduct all educational activities including supervision activities, both academic supervision and managerial supervision within the school / madrasah he leads. Principal As Supervisor serves to guide, assist and direct educators and educational staff to appreciate and implement the procedures of education to support the quality of education.